Comparison of Mental Health Nursing Student Academic Achievement and Satisfaction: Classroom Versus Online Education in Teaching Therapeutic Crisis Management Techniques. (4th March 2019) - Graber, Jennifer
Abstract: Background: Mental health nurse educators use online education in an effort to offer students the ability to practice varying skills in a safe environment. Purpose: The purpose of this study was to compare the effectiveness and student satisfaction of live classroom versus online education in delivering therapeutic crisis management skills content to pre-licensure nursing students as measured by overall grade point average (GPA), test scores, class grade, and student satisfaction survey results. Methods: This quasi-experimental, post-hoc comparative study had a two-group post-test design. The participants were pre-licensure psychiatric mental health nursing students who were presented a 30-min lecture followed by group work with case studies and interventions. Results: There were no statistically significant differences between the live classroom and online education group. Conclusions: This study indicates that therapeutic crisis management techniques can be taught a variety of ways for academic success and may validate the feasibility of online education within mental health nursing curricula.